Step up : health and physical education for Queensland - Brunetto, Frank (Port Melbourne, Vic. : Cambridge University Press, 2009)
"Step up - health and physical education for Queensland has been written by QLD teachers for QLD students in years 8-10. It builds upon the foundations established in the Health and Physical Education Key Learning Area Syllabus, and comprehensivley covers the threee core learning strantds: promoting the health of individuals and communities; developing concepts and skills for physcial activity; and enhancing personal development. Step up also explicity addresses the Essential Learnings and Standards for H & PE to assist students and teachers in meeting the Queensland Curriculum, Assessment and Reporting (QCAR) Frameworkd requirements."--Back cover.
Includes index.
For secondary school age.
System requirements: CD-ROM drive, PC: Windows 98 or higher; Pentium II 500Mhz or higher; minimum 256Mb RAM. Mac: OS 10.2 or higher; PowerMac G3 500Mhz or higher; minimum 256Mb RAM. Some resources require Microsoft Office 2003 or higher and a web browser.
Keywords: Health -- Queensland -- Textbooks; Physical education and training -- Queensland -- Textbooks